EVALUATION AND SIZING OF THE NAAMA PHOTOVOLTAIC POWER PLANT. - SULAIMAN, ABUTEIR (My University, 2023)
With the increasing demand for energy in the world in general and in Algeria in particular, renewable energies have emerged as an effective solution in promoting economic growth. At the national and international levels, renewable energies play an important role in the Algerian program dedicated to the advancement and promotion of energy efficiency, and this study concerns a comprehensive assessment of the size of photovoltaic power plant with a capacity of 20 MW located in the city of Naama according to international specifications. Therefore, we explained everything related to photovoltaic energy and the scaling of all elements of the plant, and finally, using the PVSYST software, we simulated the plant and obtained the results of the plant, and these results indicate that the performance index is good and its value is approximately 81.8% and contributed on the one hand to knowing the location of the plant in terms of energy production at the national level, and on the other hand contribute to the development of the construction of other photovoltaic plants programmed by the Algerian government. Keywords: photovoltaic power plant, performance index, sizing, renewable energies, Algerian program for energy development, PVSYST software. Résumé: Avec la demande croissante d'énergie dans le monde en général et l’Algérie en particulier, les énergies renouvelables sont apparues comme un atout efficace pour favoriser la croissance économique. Aux niveaux national et international, les énergies renouvelables jouent un rôle important dans le programme algérien dédié à l'avancement et à la promotion de l'efficacité énergétique, et cette étude concerne un dimensionnement complet de la taille de la centrale photovoltaïque d'une capacité de 20 MW située dans la ville de Naama selon le cahier des charges international. Par conséquent, nous avons expliqué tout ce qui concerne l'énergie photovoltaïque et la mise à l'échelle de tous les éléments de la centrale, et enfin, à l'aide du logiciel PVSYST, nous avons simulé la centrale et obtenu les résultats de la centrale, et ces résultats donne un bon indice de performance de 81,8% est qui a contribué d'une part à connaître l'emplacement de la centrale en termes de production d'énergie au niveau national, et d'autre part au développement de la construction d'autres centrales photovoltaïques programmées par le gouvernement algérien. Mots-clés: centrales photovoltaïques, indice de performance, dimensionnement, énergies renouvelables, programme algérien de développement énergétique, logiciel PVSYST. ملخص : مع تزايد الطلب على الطاقة في العالم بشكل عام وفي الجزائر بشكل خاص ، ظهرت الطاقات المتجددة كحل فعال في تعزيز النمو االقتصادي. على المستويين الوطني والدولي ، تلعب الطاقات المتجددة دو ًرا مهًما في البرنامج الجزائري المخصص للنهوض وتعزيز كفاءة الطاقة ، وتتعلق هذه الدراسة بتقييم شامل لحجم محطة الطاقة الكهروضوئية بقدرة 02 ميجاوات الموجودة في مدينة نعامة طبقا للمواصفات العالمية. لذلك قمنا بشرح كل ما يتعلق بالطاقة الكهروضوئية وتحجيم جميع عناصر المحطة ، وأخيرا باستخدام برنامج PVSYST قمنا بمحاكاة للمحطة و تحصلنا على نتائج المحطة ، وهذه النتائج تشير إلى أن مؤشر األداء جيد وقيمته تقارب 8..8 ٪ وساهم من جهة في معرفة موقع المحطة من حيث انتاج الطاقة على المستوى الوطني ، ومن جهة أخرى في تطوير إنشاء محطات كهروضوئية أخرى ببرمجة الحكومة الجزائرية. الكلمات المفتاحية: محطات الطاقة الكهروضوئية ، مؤشر األداء ، التحجيم ، الطاقات المتجددة ، البرنامج الجزائري لتطوير الطاقة.، برنامج .PVSYST
Keywords: photovoltaic power plant; performance index; sizing; renewable energies; Algerian program for energy development; PVSYST software